A Thematic and Visual Review of Literary Adaptations Across Film and Digital Media (Journal of Advances and Scholarly Researches in Allied Education, 2026)
This paper examines the thematic and visual dimensions of literary adaptations across film and digital media, focusing on how narratives are transformed when they move from written texts to audiovisual forms. Drawing on contemporary adaptation theory, the study explores how filmmakers and digital creators reinterpret literary works through thematic reconfiguration, visual storytelling techniques, and medium-specific narrative structures. The paper analyzes how elements such as cinematography, mise-en-scène, editing, sound design, and digital technologies contribute to the visual transmutation of literary narratives, enabling textual descriptions and internal monologues to be expressed through audiovisual representation. In addition, the study investigates the challenges and creative possibilities associated with adapting literature into film and digital platforms, including narrative compression, representation of psychological depth, and the influence of technological innovation and streaming media. By examining the evolving relationship between literature and visual media, the paper highlights how adaptations function as interpretive and creative practices that reshape narrative meaning while maintaining connections to their literary sources. Ultimately, the study demonstrates that literary adaptations are not merely reproductions of original texts but dynamic reinterpretations that allow stories to remain culturally relevant across different media environments and changing audience contexts.